TELEVISION IN THE CONTEMPORARY CULTURE: THE PROBLEM OF PREPOTENCY OF PRIVATE SPACE - E.G. KUROVA (Advanced Engineering Research)
The article considers basic tendency of contemporary society (the displacement of boundaries between public and private spheres ) in the context of postmodern television culture, brings out the characteristics of contemporary televiewer’s consciousness, founds a topicality of pointed problem from the point of view of practical importance in the sphere of individual socialization.